Examination of Postgraduate Theses Designed with Qualitative Research Method Regarding Learning Disabilities: Systematic Review - Dinç, Vedat; İlik, Şerife Şenay (Fırat Üniversitesi, 2025)
The aim of this review study is to make a systematic review of the postgraduate theses on learning disabilities in Turkey between 2020-2024. The question sentence of the study was determined as “What are the current trends of the postgraduate theses on the subject of learning disabilities by researchers targeting the subject of learning disabilities with the PICOS method?”. In the study, the keywords ''learning disability'', ''learning disorder'', ''specific learning disability'', ''specific learning disability'', ''specific learning disorder'', ''specific learning disorder'' were scanned from the Council of Higher Education Thesis database. Then the data were analyzed descriptively. Research findings were presented under subcategories in line with the research questions. The findings are presented under the headings of distribution of the studies according to the type of thesis, distribution of the studies according to the year of publication, distribution of the studies according to qualitative research designs, distribution of the studies according to data collection tools, distribution of the studies according to data analysis, distribution of the studies according to the subject and results. In the study, it was found that the majority of the studies between 2020-2024 were master's theses, most of the studies were conducted in 2023 and 2024, phenomenology and case study designs were mostly preferred among the qualitative research designs of the studies, data collection tools of the studies were preferred, and data collection tools of the studies were preferred.

Bu derleme çalışmasında amaç 2020-2024 yılları aralığında Türkiye’de öğrenme güçlüğü ile ilgili nitel araştırma yöntemiyle desenlenen lisansüstü tezlerin sistematik derlemesini yapmaktır. Araştırmanın soru cümlesi PICOS yöntemi ile öğrenme güçlüğü konusunu hedef alan araştırmacıların, öğrenme güçlüğü konusu ile ilgili yapılmış olan lisansüstü tezlerin güncel eğilimleri nelerdir? olarak belirlenmiştir. Çalışmada Yükseköğretim Kurulu Tez veri tabanından ‘’öğrenme güçlüğü’’, ‘’öğrenme bozukluğu’’, ‘’özel öğrenme güçlüğü’’, ‘’özgül öğrenme güçlüğü’’, ‘’özel öğrenme bozukluğu’’, ‘’özgül öğrenme bozukluğu’’ anahtar kelimeleri taratılarak incelenmiştir. Ardından verilerin betimsel analizi yapılmıştır. Araştırma bulguları araştırma soruları doğrultusunda alt kategoriler altında sunulmuştur. Bulgular, yapılan çalışmaların tez türüne göre dağılımları, yapılan çalışmaların yayın yılına göre dağılımları, yapılan çalışmaların nitel araştırma desenlerine göre dağılımları, yapılan çalışmaların veri toplama araçlarına göre dağılımları, yapılan çalışmaların veri analizine göre dağılımları, yapılan çalışmaların konu ve sonuçlarına göre dağılımları şeklinde başlıkları altında sunulmuştur. Araştırmada, 2020-2024 yılları arasındaki çalışmaların çoğunluğunun yüksek lisans tezi olduğu, çalışmaların büyük bir bölümünün 2023 ve 2024 yılında yapıldığı, yapılan çalışmaların nitel araştırma desenlerinden en çok fenomenoloji (olgubilim) ve durum çalışması desenlerinin tercih edildiği, yapılan çalışmaların veri toplama araçlarından en çok görüşme tercih edildiği, yapılan çalışmaların analizinde en çok içerik analizinin kullanıldığı sonucuna ulaşılmıştır.
Öğrenme Güçlüğü ile İlgili Nitel Araştırma Yöntemiyle Desenlenen Lisansüstü Tezlerin İncelenmesi: Sistematik Derleme
Keywords: Applied and Developmental Psychology (Other); Uygulamalı ve Gelişimsel Psikoloji (Diğer)